The Relationship Between Learning Outcomes Of Entrepreneurial Creative Products And Entrepreneurial Readiness For Class Xii Students Of The Catering Expertise Program At Smkn 2 Pariaman - Rahmalia, Shindy Nurul; Elida, Elida (Jurnal Pendidikan Tata Boga dan Teknologi, 2022)
The background of this research is that there are still many students who do not have readiness in entrepreneurship, even though judging from the learning outcomes of Entrepreneurial Creative Products, the average student score is in the good category. The aims of the study were to describe the learning outcomes of Entrepreneurial Creative Products, to describe the entrepreneurial readiness of students in the Catering Services skill program at SMKN 2 Pariaman and to analyze the relationship between the learning outcomes of Entrepreneurial Creative Products and the entrepreneurial readiness of students in the Catering Skills Program at SMKN 2 Pariaman.This type of research is quantitative with a correlational approach. The research was conducted at SMKN 2 Pariaman. The population is all class XII students of the Catering Services skill program at SMKN 2 Pariaman with a total sample of 68 students. Sources of research data are students of class XII who have studied the subject of Creative Products Entrepreneurship in class XI. The data collection technique used a questionnaire (google form) which was measured using a Likert scale. Data analysis technique is done by correlation coefficient analysis and correlation coefficient test.The results of the study illustrate that the overall learning outcomes of Entrepreneurial Creative Products are included in the Good category with a frequency of 47 (69%), entrepreneurship readiness of students of the Catering Skills Program at SMKN 2 Pariaman as a whole is included in the high category with a frequency of 60 (88%), there is a relationship which is positive and significant between the learning outcomes of Creative Entrepreneurship Products and the readiness for entrepreneurship of class XII students of the Catering Services expertise program at SMKN 2 Pariaman by obtaining a significant value of 0.000. This means that the higher the learning outcomes of Entrepreneurial Creative Products, the higher the entrepreneurial readiness of class XII students of the Catering Services expertise program at SMKN 2 Pariaman.